2022
DOI: 10.1002/oby.23568
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis comparing the effectiveness of alternate day fasting, the 5:2 diet, and time‐restricted eating for weight loss

Abstract: Objective: The objective of this meta-analysis was to compare the effectiveness of different intermittent fasting (IF) regimens on weight loss, in the general population, and compare these to traditional caloric energy restriction (CER).Methods: Three databases were searched from 2011 to June 2021 for randomized controlled trials (RCTs) that assessed weight loss and IF, including alternate day fasting (ADF), the 5:2 diet, and time-restricted eating (TRE). A random effect network analysis was used to compare th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 62 publications
2
20
0
Order By: Relevance
“…These findings may be related to inaccurate food diary reporting in TRE trials or due to as yet unknown physiological mechanisms. Meta-analyses of RCTs has corroborated these observations showing that IF is likely to be the most effective dietary weight loss strategy, followed by CCR, and then TRE 118. Nonetheless, despite relatively modest weight reductions, TRE is associated with significant and often disproportionate improvements in cardiometabolic health.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…These findings may be related to inaccurate food diary reporting in TRE trials or due to as yet unknown physiological mechanisms. Meta-analyses of RCTs has corroborated these observations showing that IF is likely to be the most effective dietary weight loss strategy, followed by CCR, and then TRE 118. Nonetheless, despite relatively modest weight reductions, TRE is associated with significant and often disproportionate improvements in cardiometabolic health.…”
Section: Introductionmentioning
confidence: 79%
“…TRE may, therefore, be a more attractive dietary strategy for some individuals by allowing them to simply ‘watch the clock’ rather than meticulously calculate ongoing calorie consumption. This is demonstrated in meta-analysis of 24 RCTs where study retention rates used as a gross indicator of compliance were highest for TRE (94%), followed by 5:2 diet (88%) and ADF (85%) 118…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Varady and Gabel reported ADF-mediated weight loss ranging from ~3–7% in trials lasting approximately two to six months [ 11 ]. A meta-analysis by Elortegui Pascual et al [ 12 ], including 24 randomized controlled trials (RCTs), found that ADF resulted in greater weight loss than TWF and TRE. However, it was noted that the degree of weight loss between the diets was not statistically significant.…”
Section: Intra-week Fastingmentioning
confidence: 99%
“…IF comes in different forms. More common IF regimens include alternate day fasting, time restricted eating (TRE‐also referred to as time restricted fasting or TRF, especially when referring to animal studies) and whole day fasting 10–12 (Figure 1).…”
Section: Introductionmentioning
confidence: 99%